Edukasi Early Warning System Pada Perawat Terhadap Kegawatdaruratan di Rumah Sakit - Triwijayanti, Renny (Khidmah, 2024)
Background: The success of first aid in dealing with patient emergencies is very dependent on the speed and accuracy of initial detection which determines the success of nursing care for patient emergencies. Early detection of emergencies can use the Early Warning System (EWS). The aim is to provide early warning system education to nurses in hospitals in emergencies. Method. This service was carried out at the Palembang Muhamamdiyah Hospital for 33 nurses. The activity stages are implementation meetings, preparing materials and participants, education and demonstration of the EWS application. Results: It was found that there was an increase in nurses' knowledge regarding EWS. Conclusion: the EWS application makes it easier for nurses to carry out early detection of emergencies. Key words: early warning system, nurse